Pedagogies of Pluralism: Teacher Agency in Fostering Religious Moderation among Multifaith Students - Muhammad Abri Harahap; Lahmuddin Lubis; Junaidi Arsyad (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Indonesia’s religious diversity presents both a national asset and a potential source of social tension, particularly in educational settings where pluralism must be actively navigated. Despite growing scholarly interest in religious moderation, empirical research on how teachers operationalize these values in multi-religious vocational schools remains limited. This study investigates the pedagogical strategies and institutional roles teachers employ to strengthen religious moderation among students from diverse faith backgrounds. Employing a qualitative case study design, data were gathered through in-depth interviews, participant observation, focus group discussions, and document analysis involving school leaders, teachers, students, and community members across two public vocational schools in North Sumatra. The findings reveal that teachers foster moderation by embedding four core values—national commitment, religious tolerance, non-violence, and local cultural accommodation—into curricular instruction, extracurricular programs, and daily school routines. Two complementary models emerged: an accommodation-based approach prioritizing habitual coexistence and cultural kinship, and a civic–Pancasila-based model grounded in structured character education and project-based learning. Crucially, the study demonstrates that religious moderation thrives not as a standalone subject but as a lived, contextual practice sustained by teacher exemplarity and supportive school policies. These findings provide actionable implications for educational policymakers and curriculum developers aiming to institutionalize inclusive pedagogies that nurture interfaith harmony and civic cohesion in pluralistic secondary education.